Household Solid Waste Management in Different Income Levels in Eldoret Municipality -Kenya - Orori, B. O. (Africa Environmental Review Journal, 2017)
Solid wastes are materials that man and other animals discard after receiving the product utility. Solid waste materials include household garbage, food wastes, yard wastes, and demolition or construction debris. Solid waste generation is an inevitable consequence of production and consumption activities in any economy. The rate of generation of household solid waste in the developing countries is increasing with increase in population, technological development, and changes in the life styles of the people which is posing a great environmental and public health problem. With fast expansion of urban, agricultural and industrial activities spurred by rapid population growth has led to huge amount of solid wastes that pollute the environment and destroy resources. The study was conducted in Eldoret Municipality in three estates including Langas, Elgon View and Kimumu. The study aimed at determining quantity and rates of household solid wastes generated in three different residential areas of various income levels in Eldoret town. Data was collected through direct observation and use of questionnaires. The questionnaires contained both open ended and closed questions. The questionnaire was semi-structured to collect both qualitative and quantitative data. Data was analyzed using a statistical package for social scientists. The study found out that the main household solid waste materials in Eldoret are food scraps and plastics The study revealed that amounts of wastes generated increase significantly with income, with high income areas generating more waste than the low income areas. The study found out that most of the low income households had little knowledge on reduce, recover and reuse concept of waste management. The study also revealed that waste collection by the municipal council of Eldoret is still very low and people opt to individual disposal methods. The disposal methods available in Eldoret include burning in the open pits, landfills and leaving wastes scattered. The study therefore, recommended that the county government should come up with better waste collection and disposal methods and to create awareness on the importance of having a clean environment in Eldoret.